Risk factors associated with falls in the geriatric population: a review of the state of the art. (Salud, Arte y Cuidado, 2023)
The elderly population is accompanied by the impairment of many functions that decrease the risk of falls in the young population. Some of the factors that play a role in this risk are age-related, therefore considered hardly preventable. Others are recognized as potentially modifiable or preventable, such as chronic diseases, medication or the quality of care by family members or institutions. This review discusses the impact, risk factors and prevention strategies for falls in the elderly population.